Managing the Marginal: Regulating and Negotiating Decency in Vancouver's Beer Parlours, 1925-1954 - Campbell, Robert (Labour/Le Travailleur, 1999)
Little historical work has been done in Canada on public drinking in general and public drinking after prohibition in particular. For British Columbia this neglect is a real oversight because hotel saloons were transformed into hotel beer parlours after prohibition. The first parlours opened in Vancouver in 1925, and, like saloons, they catered to a working-class clientele. Parlours held sway until 1954 when a new Government Liquor Act provided for additional venues of public drinking. One did not have to sit long in a Vancouver parlour to realize that more than alcohol consumption was being regulated. Parlours also regulated class, gender and sexuality, and race. Parlour regulation is better understood as moral regulation rather than social control. Moral regulation is a useful analytical perspective because it emphasizes the dynamic qualities of regulation, the multitude of regulators, and broad conceptions of knowledge and power. Advocates of moral regulation, however, tend to deemphasize state power. I argue that the state's influence should not be minimized to a point that obscures the significance of internalization, acquiescence, and coercion. In Vancouver's beer parlours the state remained an important manager of the marginal.